Epistemology of Fatwas on Digital Transaction in Indonesia - Bashori, Akmal; Mutho'am, Mutho'am; Noor Hazlina Wan Jusoh, Wan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The shift from conventional business transactions to digital business transactions, especially for the Muslim community in Indonesia, necessitates a fast and reactive response from current laws. The theoretical argument that has been developed thus far is that the fatwa is the most appropriate legal tool for Muslim communities to respond to the rapid development of digital business. Nevertheless, do the existing fatwas fulfill legal needs as expected in this era of digital transactions? Hence, this paper discusses digital transaction fatwas within the framework of Islamic legal epistemology, especially fatwas from the National Shariah Council–Indonesian Ulama Council. The research method uses normative juridical with a conceptual and historical-uṣūliyah approach. This research finds that the contemporary fatwa epistemology of the National Shariah Council–Indonesian Ulama Council in terms of digital transactions employs istiṣlāhī arguments. This is shown by the proposition that fiqh rules are more dominant than textual ones. Moreover, the arguments in the fatwa of the National Shariah Council–Indonesian Ulama Council provide signs of benefit as the estuary of maqāṣid syarī'ah. The consistency of the use of legal methodology utilized by the National Shariah Council–Indonesian Ulama Council in fatwas on digital transactions is shown in the structure and utilization of al-nuṣūṣ al-shariah arguments, the opinions of ulama, and the rules of fiqh, which are expanded from the five rules of fiqh into eight rules. These fatwas are reliable and valid in terms of dictum and method, thus supporting the development of the current digital transactions.